Experimental Investigation of Ground and Air Temperature Fields of a Cold-Region Road Tunnel in NW China - Hao Wu; Yujian Zhong; Wei Xu; Wangshuaiyin Shi; Xinghao Shi; Tong Liu (Advances in Civil Engineering)
To fully understand the temperature distribution of cold regions and the variation law of temperature fields in cold-region tunnels, this paper presents a case-history study on a tunnel located on the eastern Qinghai-Tibet Plateau, China. The conclusion is as follows: the temperature outside the tunnel and the ambient temperature are affected by wind speed and light. The law of the temperature field in the tunnel is greatly affected by wind speed and wind direction. According to the field test, the wind speed in the tunnel is about 2.8 m/s in winter, and the daily average temperature at the exit of the tunnel is basically lower than that at the entrance. From the central to the entrance, the temperature in the tunnel decreases by 0.11°C every 10 meters along the longitudinal direction; from the central to the exit, the temperature in the tunnel increases by 0.07°C every 10 meters. In this regard, for the problems of lining frost damage and central drainage pipe freezing, it is suggested to adopt the way of heating and drainage, but heating the freezing area outside the drainage pipe should be avoided. The test results can provide references for the design, construction, and research of the temperature field of the tunnel antifreezing system in the cold region. It is hoped that the test results can be useful in the design and construction of frost damage prevention systems and the investigation of temperature fields in cold-region tunnels.